The Impact of Compensation and Non-Physical Work Environment on Employee Performance at CV. Sumber Makmur Indonesia, West Jakarta - Faryina, Laulia; Astuti, Widia (Pascasarjana Universitas Pasundan, 2025)
This study aims to analyze the effect of compensation and non-physical work environment on employee performance at CV. Sumber Makmur Indonesia, both partially and simultaneously. Using a saturated sampling technique with 60 employees, data was collected through observation and questionnaires. Multiple linear regression results indicate that compensation (0.126) and non-physical work environment (0.337) have a positive effect on employee performance. The determination test (R²) of 24.4% shows the contribution of independent variables to employee performance. The t-test confirms that compensation (t-count 3.674 > t-table 2.002) and non-physical work environment (t-count 4.229 > t-table 2.002) have a significant effect, while the F-test (9.174 > 3.16) indicates a significant simultaneous influence